Clarithromycin Versus Metronidazole as First-line Helicobacter pylori Eradication. Issue 6 (July 2015) - Nishizawa, Toshihiro; Maekawa, Takama; Watanabe, Noriko; Harada, Naohiko; Hosoda, Yasuo; Yoshinaga, Masahiro; Yoshio, Toshiyuki; Ohta, Hajime; Inoue, Syuuji; Toyokawa, Tatsuya; Yamashita, Haruhiro; Saito, Hiroki; et al.
<x xml:space="preserve">Abstract</x> Background: Helicobacter pylori eradication rates achieved with a first-line regimen of clarithromycin (CLR) combined with amoxicillin (AMX) and a proton pump inhibitor have recently fallen to ⩽80% because of the increasing incidence of CLR resistance in Japan. This randomized multicenter trial aimed to compare the eradication success of 2 first-line triple therapy regimens: rabeprazole, amoxicillin, and clarithromycin (RAC) versus rabeprazole, amoxicillin, and metronidazole (RAM). Methods: A total of 124 consecutive patients infected with H. pylori were randomized into one of two 7-day therapeutic regimens: RAC (n=60) or RAM (n=64). Eradication was confirmed by the 13C-urea breath test. Adverse effects were also assessed. Results: Intention-to-treat and per protocol H. pylori eradication rates were 73.3%/77.2% in the RAC group and 90.6%/93.5% in the RAM group. The eradication rate of RAM therapy was significantly higher than that of RAC therapy. CLR, metronidazole, and AMX resistance was found in 36.2%, 2.1%, and 0% of patients, respectively. In addition, no relevant differences in adverse effects were observed. Conclusions: Metronidazole-based therapy (RAM) was superior to standard CLR-based therapy (RAC) for first-line H. pylori eradication. This reflects the progressive increase in CLR resistance observed in Japan.